Effect of using anti-wear and friction modifier-based additives on tribological performance of engine lubricants - Arman, Salih; Mohd Nadzeri, Omar; Nasrul Hadi, Johari; Mohd Hasnun, Arif Hassan (Institution of Engineering and Technology, 2022)
Lubricant is used to decrease wear on two surfaces that come into contact with each other, and additives can aid to improve the lubricant's performance. Engine oil is the lubricant that we use in combustion engines, and ex-ternal additives that are available on the market can be added to the engine oil to improve its performance. The purpose of this study is to see how ex-ternal additives affect the tribological performance of engine lubricants. The performance of three lubricant samples was investigated in this study: commercial engine oil (SAE10W-30), engine oil mixed with friction modifier additives, and engine oil mixed with anti-wear and extreme pressure additives. The mixtures' viscosity, coefficient of friction (COF), and wear scar diameter (WSD) were determined using viscometer, four-ball tester, and high-performance microscope. The findings show that the mixes behave differently than commercial oil. Even though adding additives to engine oil is sup-posed to boost performance, the flash temperature parameter (FTP) deter-mined from WSD, and the frictional behaviour analysis demonstrate otherwise. Chemical interactions between additives may occur because of the mixing, causing the oil's structure to change. Using commercial oil alone, according to this study, is optimal for extending the life of a combustion engine.